OPTIMALISASI PEMBANGUNAN PROYEK APARTEMEN SGC CIBUBUR DENGAN MENGGUNAKAN METODE PRECEDENCE DIAGRAM METHOD (PDM) - ARIZAL NURHIDAYAT; BASUKI ARIANTO; W. TEDJA BHIRAWA (JURNAL TEKNIK INDUSTRI, 2021)
PT JG Tbk which is engaged in building construction. This company was founded in 1980, although it has been around for decades, and has experienced various types of building construction models. Companies often experience work delays at the time of implementation, because the delay in project work is not carried out right at the time of the agreement. Therefore, it is necessary to analyze the project scheduling so that it can be seen how long the project can be completed. The stages at the completion of the SGC project on floors 3 to 5, namely: determining the stages of activities, compiling new networks, making precedence diagram method activities, estimating manpower costs. In the case of the construction of the SGC Cibubur apartment floors 3 to 5 floors. With scheduling data from the company, which is for 497 days, the wages of masons, workers and foremen are Rp. 5,886,132,300.00 with the calculation of wages for mason workers, kenek and foremen using the PDM method of Rp. 5,401,080,000.00 savings in labor wages to Rp. 485,052,300.00 from the results of calculations using the PDM method is far more optimal than the calculations used by the company. Keywords: Project, Critical Path, Networking Diagram, Precedence Diagram Method (PDM)